Pengaruh penggunaan dompet digital (ShopeePay) terhadap perilaku konsumsi mahasiswa (Studi pada mahasiswa Universitas Jambi Fakultas Ekonomi dan Bisnis) - Nurhayani, Nurhayani; Anindito, Ridho; Kusuma Edy, Jaya (Jurnal Paradigma Ekonomika, 2024)
This study aims to analyze the characteristics of ShopeePay digital wallet users as a means of payment among students of the Faculty of Economics and Business, University of Jambi and how promotion, convenience, security, and pocket money in using ShopeePay affect consumption behavior among students of the Faculty of Economics and Business, University of Jambi. The method used is descriptive and Binary Logistic Regression using SPSS statistical software version 25.0. The results of this study based on the characteristics of the respondents, show that the majority of ShopeePay users are female and the average user is 22 years old, the average monthly pocket money of respondents is IDR 748,558. The amount of ShopeePay expenditure per month averages IDR 297,596, the frequency of using ShopeePay averages 4.72 times per month and the products purchased are mostly clothing. Based on the Wald test, the results show that convenience, security, and pocket money influence student consumption behavior, while promotion does not. Based on the omnibus model fit test, promotion, convenience, security, and pocket money have an overall effect on the consumption behavior of students of the Faculty of Economics and Business, University of Jambi.